2007
DOI: 10.1074/jbc.m706744200
|View full text |Cite
|
Sign up to set email alerts
|

Quail Sulf1 Function Requires Asparagine-linked Glycosylation

Abstract: The heparan sulfate endosulfatases Sulf1 and Sulf2 are cellsurface enzymes that control growth factor signaling through regulation of the 6-O-sulfation states of cell-surface and matrix heparan sulfate proteoglycans. Here, we report that quail Sulf1 (QSulf1) is an asparagine-linked glycosylated protein. Domain mapping studies in combination with a protein glycosylation prediction program identified multiple asparagine-linked glycosylation sites in the enzymatic and C-terminal domains. Glycosylation inhibitor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…For example, in common with other sulfatases (37,38), the activity of both Sulfs relies on the conversion of a highly conserved cysteine within the catalytic domain into C␣-formylglycine, the site at which sulfate is directly bound (7,8,33). In addition, N-linked glycosylation is required for QSulf-1 activity (39). In contrast to this information about post-translational modifications, little has been reported concerning the proteolytic processing of these enzymes.…”
Section: Discussionmentioning
confidence: 82%
“…For example, in common with other sulfatases (37,38), the activity of both Sulfs relies on the conversion of a highly conserved cysteine within the catalytic domain into C␣-formylglycine, the site at which sulfate is directly bound (7,8,33). In addition, N-linked glycosylation is required for QSulf-1 activity (39). In contrast to this information about post-translational modifications, little has been reported concerning the proteolytic processing of these enzymes.…”
Section: Discussionmentioning
confidence: 82%
“…Both SULFs are modified by asparagine-linked glycans before secretion, perhaps at 6-12 sites, and various varieties have been discovered in cell medium[14]. N -linked glycosylation of quail SULF1 appears essential for secretion, membrane targeting, and enzyme activity[17]. Little conservation exists among potential glycosylation sites between species.…”
Section: Sulf1 and Sulf2 Domain Structure Substrate Specificity And mentioning
confidence: 99%
“…In the case of the quail ortholog, QSulf1, two N-glycosylation sites are predicted in the HD (positions 527 and 620). A systematic analysis of the N-glycosylation of QSulf1 has revealed that neither of these two sites are utilized in vivo (38). Furthermore, protein N-glycosylation was shown to be essential for enzymatic activity and membrane targeting of QSulf1.…”
Section: Generation and Characterization Of Sulf1 Deletion Mutants-mentioning
confidence: 99%
“…Based on glycosylation analysis of human Sulf1 (see above) and previous results from the quail ortholog QSulf1 (38), the absence of glycan structures within the HD enables heterologous expression of the isolated HD in E. coli. Therefore, N-terminal GST fusion constructs GST-HD, GST-HDB, and GST-HDC were generated, containing either the entire HD of human Sulf1 or parts thereof, corresponding to the above described Sulf1 deletion mutants (Fig.…”
Section: Generation and Characterization Of Sulf1 Deletion Mutants-mentioning
confidence: 99%